Beyond the classroom: Fostering English communication skills in vocational education through podcasting and radio broadcasting - Hamid, Syifa Fadhilah; Forsia, Lastry; Isnaniah, Isnaniah (Jurnal Pembelajaran Pemberdayaan Masyarakat (JP2M), 2024)
Addressing the challenge of developing effective English communication skills in vocational education, this study explores the integration of podcasting and radio broadcasting as an alternative to traditional classrooms. The goal is to provide vocational students with a more immersive and practical learning experience in line with communicative language teaching principles. Putra Rifara Vocational School initiated a Radio Podcast program, emphasizing technological proficiency. A seminar, "Hosting Podcast in English," was conducted to train students in podcasting and radio broadcasting. Practical exercises were included to enhance language skills, including articulation, opinion expression, and real-time dialogues. A needs analysis revealed students' interest in podcasts as learning material, with challenges related to internet limitations. The initiative positively impacted students' attitudes, behaviors, linguistic proficiency, and soft skills development. Ongoing training and mentorship are recommended to empower students in confidently hosting English podcasts. This initiative demonstrates the potential of podcasting and radio broadcasting to enrich English language learning in vocational education, contributing to linguistic proficiency and soft skills development within the educational environment. Considerations for improving internet accessibility and guiding podcast selection are recommended for future implementations.